2021
DOI: 10.1007/s10845-020-01717-4
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for multi-dimensional optimisation and predictive visualisation of laser machining

Abstract: Interactions between light and matter during short-pulse laser materials processing are highly nonlinear, and hence acutely sensitive to laser parameters such as the pulse energy, repetition rate, and number of pulses used. Due to this complexity, simulation approaches based on calculation of the underlying physical principles can often only provide a qualitative understanding of the inter-relationships between these parameters. An alternative approach such as parameter optimisation, often requires a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…GANs were already utilised as a predictive visualisation method in laser machining. Laser-ablated topographies were recreated based on spatial laser intensity profiles [16] or by transforming the key laser parameters into predicted 3D surface profiles [17].…”
Section: Introductionmentioning
confidence: 99%
“…GANs were already utilised as a predictive visualisation method in laser machining. Laser-ablated topographies were recreated based on spatial laser intensity profiles [16] or by transforming the key laser parameters into predicted 3D surface profiles [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the USW process the input parameters take integer values, therefore, the parameter space is discrete. Once trained, interrogating the GA–ANN ensemble to retrieve LSS, defect and repeatability predictions for the entire bounded parameter space took less than 180 s. A similar approach was implemented by McDonnell et al ( 2021 ) when optimising a multi-objective laser machining process, where the optimised process was superior to the observed DoE data. In this study, the predictions were formatted to return the input parameters corresponding to the maximum LSS achievable when the model predicts the process to produce zero defects while having class one repeatability.…”
Section: Machine Learningmentioning
confidence: 99%
“…The study found ANN modelling provided a more accurate prediction. Similarly, McDonnell et al ( 2021 ) compared the performance of Gaussian process regression (GPR), support vector machines (SVM), and ANN’s for the multi-objective optimisation of a laser machining process identifying ANN as the superior machine learning method. Seyyedian Choobi et al ( 2012 ) used forty-one training samples to train an ANN with fifteen, twenty and twenty-five neurons in the first, second and third hidden layers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the forward transmission process, the signal is processed layer by layer from the input layer through the hidden layer to the output layer. If the output layer cannot obtain the desired output, the signal is transmitted to back propagation, and the weight and threshold are adjusted according to the prediction error, so that the output of BPNN continues to be close to the expected output [13][14][15]. It is known that BPNN containing a hidden layer has sufficient accuracy to approximate any continuous function [16].…”
Section: Error Correction Algorithmmentioning
confidence: 99%
“…After the training, the E i and the average absolute error (AAE) E s of the output values of the MPGA-BPNN relative to the actual measurement value are obtained by (15) and (19). To evaluate the error correction ability of MPGA-BPNN, E s of the ILA, BPNN, and SPGA-BPNN are introduced as follows: Shock and Vibration 7…”
Section: Ga Evaluationmentioning
confidence: 99%